Iowa seasonal report, fall 1991, contributed by Diane C. Porter, December 1, 1991 - Porter, Diane C.et al (1991)
List of birds and locations contributed by Diane C. Porter. The report includes descriptions of several birds. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed